The Effect Of Study Habits And Self-Regulation On Student Study Presentation At MTS Al-Ikhwan Gresik - Riyyatul Hamdiyah; Didit Darmawan (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
The desire to learn results in study habits in such a way and will have a balanced impact on learning achievement or not. This research aims to determine the influence of study habits and self-regulation on student learning achievement at MTs. Al-Ikhwan, Gresik. This research is quantitative research involving two independent variables (study habits and self-regulation) on the dependent variable (learning achievement). The population of this research is aimed at MTs students. Al-Ikhwan, Gresik. The sampling technique is random. Next, this research data will be analysis using multiple linear regression. The results of this research indicate that study habits and self-regulation have a significant effect on the learning achievement of MTs students. Al-Ikhwan Gresik. Study habits include activities and strategies that students apply during the learning process, while self-regulation includes students' ability to plan, monitor and evaluate themselves. These results can provide a basis for educational programs on developing study habits and increasing student self-regulation.